Investigation on foundation pit uplift mechanism and tunnel response induced by deep excavation under complex support system: A case study - Zhiguo Zhang; Jian Wei; Junjie Li; Linlong Mu; Wei Wo; Yin Ni (Underground Space)
Pit excavation work often occurs directly above metro tunnels, causing adverse effects on the underlying existing operational shield tunnel. Current simplified solutions mainly adopt stress release method to reflect excavation of foundation pit, which is inappropriate for large soil uplift. A two-stage analysis based on modified Sagaseta solution with displacement-controlled boundary condition and tunnel-soil coordinated constrain is promoted for estimating the mechanical behavior of tunnel with joints. Specifically, the modified Sagaseta solution including gravity effects is firstly used to obtain the soil greenfield displacement caused by foundation pit excavation. Secondly, the Pasternak foundation model, incorporating tunnel-soil ellipse-shaped deformation, combines a variable stiffness Timoshenko beam at tunnel joints and ultimately obtains the tunnel displacement curve. Furthermore, a three-dimensional numerical simulation is also conducted for Jinqiao metro superstructure excavation project that involves a foundation pit situated directly above an existing metro tunnel. The feasibility of simplified solutions is verified with numerical simulation solutions and an engineering case. For investigating the key parameters, the parametric analyses are conducted, indicating that the greenfield displacement is highly related to modified uneven convergence Sagaseta solution. The ignoration of excavation width will overestimate the tunnel displacement as plane strain condition. Both equivalent bending and shear stiffness can only influence corresponding bending and shear tunnel deformation.